1958
DOI: 10.1099/00221287-19-3-462
|View full text |Cite
|
Sign up to set email alerts
|

Some Studies on the Occurrence and Properties of a Large Gram-Negative Coccus from the Rumen

Abstract: SUMMARY: A large Gram-negative coccus was isolated in a lactate-containing medium from the rumen of young calves. This organism is anaerobic and ferments only lactate, glucose, fructose, maltose, sucrose, mannitol and sorbitol. The coccus is found in large numbers (c. lOg/ml.) in the rumen contents of young calves, but is present only in small numbers or is absent from the rumens of older cattle and sheep. An attempt made to establish the organism in large numbers in a sheep rumen was unsuccessful. The possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1960
1960
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…Portions of protozoal suspensions were inoculated into the semisolid medium of Hobson, Mann & Oxford (1958) (b) Incubation with soluble sugars. A suspension of protozoa which had been starved for 36 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Portions of protozoal suspensions were inoculated into the semisolid medium of Hobson, Mann & Oxford (1958) (b) Incubation with soluble sugars. A suspension of protozoa which had been starved for 36 hr.…”
Section: Methodsmentioning
confidence: 99%
“…4. (50), has been detected in intestinal contents and feces of ruminants (20,24,26), swine (1,23,32,58), and humans (56,59). Results from these studies suggest that M. elsdenii might colonize intestinal mucosal surfaces (Table 3), a habitat where microbial biofilms are likely sites of genetic and physiological exchanges.…”
Section: Fig 5 Pcr Assays To Identify Tet(o) Tet(w)mentioning
confidence: 99%
“…Serological techniques showed that different morphological types of rumen bacteria, observed in viuo, were related to pure cultures of known micro-organisms cultured in vitro (Hobson et al, 1955(Hobson et al, , 1958(Hobson et al, , 1962Hobson & Mann, 1957). Serological evidence also led Jarvis (1967) to suggest the existence of two different species within the genus Ruminococcus, and enabled him and his co-workers to observe diurnal variations in ruminal numbers of cellulolytic cocci by using fluorescent antisera (Jarvis et al, 1967).…”
Section: G P H a Z L E W O O D A N D Othersmentioning
confidence: 99%